The relationship between political stability and foreign direct investment in Iraq: An analytical study for the period (2004-2022) (Journal of Imam Al-Kadhim College, 2026)
This research analyzes the relationship between political stability and foreign direct investment, as there is a reciprocal relationship between the two variables in Iraq, especially after 2003, in light of the opening up of the Iraqi economy and the increase in foreign direct investment flows amidst the political transformations that Iraq witnessed, Therefore, there is a statistically significant relationship between the level of political stability and foreign direct investment, as an improved political and institutional environment in Iraq contributes to increased foreign direct investment flows into its economy by increasing foreign investors' confidence in the Iraqi political environment, There is also an indirect effect of foreign direct investment flows into Iraq on its political stability, by strengthening the foundations of the macroeconomy and thus positively impacting the strengthening and stability of the political environment, The research adopted the descriptive analytical approach to present the theoretical framework of the concepts of political stability and foreign direct investment, while formulating standard models to measure the relationship of influence between the two variables in Iraq.
Keywords: Political Stability, Foreign direct investment, Political economy, Iraq; Political Stability; Foreign direct investment; Political economy; Iraq